Cobalt(III), Nickel(II) and Copper(II) Complexes of Schiff Base Ligand 5-Methoxy-2-[(E)-{[2-(thiophen-2-yl)ethyl]imino}methyl]phenol: Synthesis, Characterization, Biological Applications and Docking Studies - Latha, R.; Vijayakumar, G.R.; Suchetan, P.A.; Sreenivasa, S.; Shivaraja, G.; Thippeswamy, B. (Asian Journal of Chemistry, 2025)
Schiff base ligand, 5-methoxy-2-[(E)-{[2-(thiophen-2-yl)ethyl]imino}methyl]phenol (LH) and its cobalt(III), nickel(II) and copper(II) metal complexes viz., Co(L)3, Ni(L)2, Cu(L)2 were synthesized and characterized. The structure of the ligand was established from the X-ray diffraction studies including other conventional techniques viz., FT-IR, UV-visible, 1H NMR, 13C NMR and Mass studies. Complexes of the ligand LH were confirmed through FT-IR, UV-visible and CHN analysis. The ligand (LH) and its metal complexes were evaluated for their antimicrobial and antidiabetic potential, supported by a comprehensive computational molecular docking study. Docking simulations demonstrated strong and favourable binding interactions of the ligand and its complexes with major antimicrobial proteins, DNA gyrase and cytochrome P450 14α-sterol demethylase, as well as antidiabetic targets, α-amylase and α-glucosidase, thereby supporting the experimental findings. The antimicrobial activity was assessed using the agar well diffusion method against bacterial strains Staphylococcus aureus and Escherichia coli, and fungal strains Aspergillus flavus and Pichia anomala. Antidiabetic activity was evaluated through in vitro α-amylase and α-glucosidase inhibition assays. The results indicated that both the ligand and its metal complexes exhibited moderate to good antibacterial and antifungal activities. However, in antidiabetic studies, the Cu(L)2 complex showed negligible inhibitory activity, while the remaining complexes displayed appreciable effects. Among all the tested compounds, the Co(L)3 complex emerged as the most promising antidiabetic agent, exhibiting significant inhibition of both α-amylase and α-glucosidase enzymes. Overall, the experimental antimicrobial and antidiabetic outcomes showed strong agreement with the molecular docking results, underscoring the reliability of computational predictions in rationalizing the biological behaviour of the synthesized compounds.